Modelling Fault Scarp Degradation to Determine Earthquake History on the Muztagh Ata and Tahman Faults in the Chinese Pamir - Lu, Lejun; Zhou, Yu; Zhang, Peizhen; Cheng, Xiao (Frontiers in Earth Science, 2022)
The frequency of earthquakes on active faults is usually revealed by palaeoseismic trenching and geological dating. Nonetheless, field trenching and sampling are sometimes limited by difficulties in logistics, therefore impeding palaeoseismological studies. As surface rupture earthquakes create fault scarps that evolve with time, they may also provide important information about the timing of earthquakes. In this study, we provide a new approach to determine earthquake history based on the morphology of fault scarps. We select the Muztagh Ata and Tahman normal faults in the Chinese Pamir as a test area, on which fault scarps are well preserved but the earthquake history has not been quantified yet. We first simulate fault scarp degradation using a nonlinear transport model to obtain the empirical relationship between scarp width and its evolution time. We then measure 68 fault scarps from high-resolution topographic data derived from WorldView-2 stereo imagery. The measured fault scarps are clustered in four groups, each group possibly representing one earthquake event. Combining the time-width relationship and scarp width measurements, we infer that four earthquakes occurred at 0.1±0.4 kyrs before the present (BP), 2.1±0.5 kyrs BP, 2.9±0.4 kyrs BP and 4.9±0.5 kyrs BP, respectively. The first event is likely to be the most recent earthquake occurred on the faults, i.e., the 1895 Tashkurgan earthquake ( ∼0.13 kyrs BP). Based on the estimated earthquake recurrence intervals and vertical offsets, we obtain a vertical slip rate of 2.2±0.3 mm/yr on the Muztagh Ata and Tahman faults, conforming to previous geological rate estimates.